2006
DOI: 10.1080/03079450500465692
|View full text |Cite
|
Sign up to set email alerts
|

Observations on detection, excretion and transmission of pigeon circovirus in adult, young and embryonic pigeons

Abstract: Infections with pigeon circovirus (PiCV) occur in young racing pigeons and pigeons raised for meat production and have been reported worldwide, but relatively little is known about the disease induced by PiCV infection. The aim of this study was to investigate how PiCV is transmitted. Using a sensitive polymerase chain reaction (PCR) test, the presence of PiCV was investigated in a wide range of samples from adult pigeons, embryos, breeders and young birds, which were derived from a racing loft that had a clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 19 publications
0
45
0
Order By: Relevance
“…In both psittacine and columbid birds with circovirus infection, psittacine beak and feather disease virus (BFDV) and pigeon circovirus (PiCV) have been suspected to be probable vertical transmission (Latimer et al, 1991;Paré et al, 1999). Recently, PiCV DNA was detected in embryos before hatching, and the ovary and testis of adult birds suggesting a vertical transmission (Duchatel et al, 2006). In addition, BFDV DNA was detected in both embryonated and nonembryonated budgerigar eggs, suggesting that the BFDV can be transmitted vertically (Rahaus et al, 2008).…”
Section: Flocksmentioning
confidence: 99%
“…In both psittacine and columbid birds with circovirus infection, psittacine beak and feather disease virus (BFDV) and pigeon circovirus (PiCV) have been suspected to be probable vertical transmission (Latimer et al, 1991;Paré et al, 1999). Recently, PiCV DNA was detected in embryos before hatching, and the ovary and testis of adult birds suggesting a vertical transmission (Duchatel et al, 2006). In addition, BFDV DNA was detected in both embryonated and nonembryonated budgerigar eggs, suggesting that the BFDV can be transmitted vertically (Rahaus et al, 2008).…”
Section: Flocksmentioning
confidence: 99%
“…PiCV was first documented in Canada in 1986 (Woods et al, 1994); since then, several outbreaks have been reported in many countries, including Northern Ireland (Smyth & Carroll, 1995;Todd et al, 2001), England (Gough & Drury, 1996), Germany (Mankertz et al, 2000;Raue et al, 2005;Soike, 1997), France (Abadie et al, 2001), Belgium (Duchatel et al, 2006), China (Yu et al, 2009), Hungary (Cságola et al, 2012 and Italy (Coletti et al, 2000;Franciosini et al, 2005). A comprehensive study has demonstrated that PiCV infection is associated with a multifactorial disease known as young pigeon disease syndrome (YPDS) possibly by inducing immunosuppression in infected birds (Raue et al, 2005;Schmidt et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Pigeon circovirus infections are very common in the domestic pigeon population, and their clinical form occurring in young birds is called Young Pigeon Disease Syndrome (YPDS) (Smyth and Carroll, 1995;Paré et al, 1999;Raue et al, 2005;Duchatel et al, 2005Duchatel et al, , 2006Zhang et al, 2011;Cságola et al, 2012;Stenzel et al, 2012). Circoviral infection in pigeons can be manifested in a wide range of signs including weight loss, decrease in racing performance, respiratory problems, diarrhoea, and occasional problems with plumage development (Raue et al, 2005).…”
mentioning
confidence: 99%